The weight of reasons a framework for ethics - Tucker, Chris 1981- (Oxford University Press, 2025)
In 'The Weight of Reasons', Chris Tucker offers a comprehensive approach to weighing reasons, proposing a new model, Dual Scale, that illuminates how reasons interact to determine whether an action is permissible, required, and/or supererogatory.
Includes bibliographical references and index
Keywords: Normativity (Ethics); Decision making / Moral and ethical aspects; Philosophy; Ethics & moral philosophy